Biomimetic synthesis of selenium nanoparticles using cell-free extract of microbacterium sp ARB05 - Prasad, K. S.; Vyas, P.; Prajapati, V.; Patel, P.; Selvaraj, K. (Micro & Nano Letters, 2012)
This Letter is a novel approach to synthesise a bio-functionalised selenium nanoparticles using cell-free extract of selenium-resistant bacterial isolate. Phylogenetic analysis of isolate suggested its close similarity with Microbacterium luteolum (Y17235.1) and Microbacterium oxydans str. TPL09 (EU373379.1) while it was distantly related to Microbacterium dextranolyticum (Y17230.1). Selenium colloidal solution exhibited an absorption maximum at 300 nm and gave emission maximum at 590 nm. Transmission electron microscopy followed by selected area electron diffraction pattern analysis indicated the formation of spherical, polydispersed, crystalline, Se nanoparticles of diameter ranging from similar to 30 to 150 nm. X-ray diffraction results showed 111, 200 and 220 planes of face-centred cubic selenium. Energy dispersive analysis of X-rays confirmed the presence of selenium in nanosphere. Selenium nanoparticles synthesised in this manner can be studied for chemo-prevention as well as its fluorescent property can be utilised for molecular diagnostics in cancer research.

Synthesis of water soluble CdS nanoparticles and study of their DNA damage activity - Prasad, K. S.; Amin, T.; Katuva, S.; Kumari, Madhu; Selvaraj, Kaliaperumal (Arabian Journal of Chemistry, 2017)
This study reports a novel method for preparation of water soluble CdS nanoparticles using leaf extract of a plant, Asparagus racemosus. The extract of the leaf tissue which worked as a stabilizing and capping agent, assisted the formation of nanoparticles. Nanoparticles were characterized using a UV–vis spectrophotometer, Photoluminescence, TEM, EDAX, XRD and FT-IR. Transmission electron microscopy followed by selected area electron diffraction pattern analysis indicated the formation of spherical, polydispersed, crystalline, CdS of diameter ranging from 2 to 8 nm. X-ray diffraction studies showed the formation of 1 1 1, 2 2 0 and 3 1 1 planes of face-centered cubic (fcc) CdS. EDAX analysis confirmed the presence of Cd and S in nanosphere. The cytotoxicity test using MTT assay as well as DNA damage analysis using comet assay revealed that synthesized nano CdS quantum dots (QDs) caused less DNA damage and cell death of lymphocytes than pure CdS nanoparticles.

Nanoparticles based adsorbent for removal of arsenic from aqueous solution - Srivastava, A.; Selvaraj, K.; Prasad, K. S. (Asian Journal of Water, Environment and Pollution, 2019)
Arsenic is a metalloid which poses a risk on water quality, a severe health problem for human and serious impact on environment. Occurrence of arsenic in natural environment may be due to natural processes or due to anthropogenic activities. Removal of arsenic can be done by many different techniques like adsorption, precipitation, flotation, ion exchange etc. Among them adsorption is widely used for removal of heavy metals from water due to its simplicity; also it’s cost effective. The aim of the study is to evaluate the potential of nanoadsorbent for arsenic removal. A number of potent adsorbent have been developed from metal, carbon and oxide based nanoparticle for enhancing the adsorption capacity and removal capacity of arsenic from aqueous solution. A short overview of nanoadsorbent for arsenic removal from aqueous solution has been discussed in this review article.